Powerful Antibacterial for Wound Healing using Betel Leaf Extract: Antibakteri Ampuh untuk Penyembuhan Luka menggunakan Ekstrak Daun Sirih - Hida Salmah Fajriati; Nurul Azizah (Academia Open, 2024)
This study investigates the antibacterial properties of betel leaf (Piper Betle L) extract on suture wound infections caused by Staphylococcus aureus. Using 25 Webster mice divided into five groups, the research compared the healing effects of 5%, 10%, and 15% betel leaf extract against a control group and a gentamicin antibiotic group over 8 days. Results, measured with the REEDA scale, indicated that the 15% extract was most effective, achieving optimal healing by the eighth day. These findings suggest that betel leaf extract, particularly at higher concentrations, could serve as a potent alternative to traditional antibiotics for treating bacterial wound infections. Highlights: 15% Extract Most Effective: Achieved complete healing by eighth day. Comparative Study: Betel leaf extract vs. control and gentamicin. Antibacterial Alternative: Potential for treating bacterial wound infections. Keywords: Betel leaf extract, Piper Betle L, wound infection, Staphylococcus aureus, antibacterial